PENGARUH RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP PERTUMBUHAN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Jihan Lestiana (Jurnal Ilmu Akuntansi, 2022)
This study aims to determine how the effect of the liquidity ratio as proxied by the Current Ratio and the solvency ratio as proxied by Debt to Total Assets on profit growth partially or partially. Along with the additional moderating variable, namely company size, which will strengthen or weaken the relationship between the Current Ratio and Debt to Total Assets on profit growth in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses quantitative research methods with an associative approach. The research population was 26 companies and 14 companies were used as research samples with a sample selection technique using purposive sampling technique. Theoretically, it is hoped that the results of this study can add knowledge and insight into profit growth using financial ratios, it is also hoped that this research can be useful as a reference source for further research. Practical usefulness Can be used as additional information in knowing the financial condition of the company. For investors, as information before making an investment, as well as for creditors, to find out the company's financial condition before making a loan to the company. For the author, it is hoped that the results of this study can add to the knowledge of more in-depth research and can be applied to the theory that has been obtained during learning in college. The results showed that the Current Ratio and Debt to Total Assets partially had no significant effect on profit growth. Meanwhile, simultaneously Current Ratio and Debt to Total Assets have a positive effect on profit growth. Then, the moderating variable shows that company size cannot moderate the relationship between Current Ratio and Debt to Total Assets on company profit growth.